Thermally conductive composition and thermally conductive member
By using a methacryloyl polysiloxane compound and a hydrosilylation catalyst in a thermally conductive silicone composition, the problem of increased hardness of the thermally conductive composition in a high-temperature environment is solved, and good softness and flexibility at high temperatures are achieved. Heat resistance.
Patent Information
- Application Number
- CN202380046100.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-06-16
- Publication Date
- 2025-01-21
AI Technical Summary
When the conventional thermally conductive silicone composition is used in a high temperature environment of 150°C or above, the hardness increases, resulting in an increase in thermal resistance and peeling of the heat generator or heat dissipation body.
A polysiloxane compound having a methacryloyl group is used as a component of the composition, and the addition reaction is promoted by a hydrosilylation catalyst to control the molecular weight and cross-linking density to suppress an increase in hardness.
In high-temperature environments above 150°C, it can effectively suppress the increase in hardness of thermally conductive components, maintain good flexibility and heat resistance, and avoid increased thermal resistance and peeling.
Smart Images

Figure BDA0005179217650000111 
Figure BDA0005179217650000241 
Figure BDA0005179217650000251
Abstract
Description
Technical Field
[0001] The present invention relates to a thermally conductive composition and a thermally conductive component. Background Art
[0002] As thermally conductive compositions, curable and liquid ones are widely known, for example, they are filled between a heating element and a radiator, and then cured to form a cured product, and used as thermally conductive components such as heat dissipation gap fillers that transfer heat generated by the heating element to the radiator. In the past, as thermally conductive compositions, silicone thermally conductive compositions containing organopolysiloxane and thermally conductive fillers were widely used.
[0003] In recent years, the market has been growing steadily with the production of electric vehicles, and the electric equipment has been developed to improve fuel efficiency and safety. The demand for automatic assembly of automotive electric components has increased, and the demand for liquid heat dissipation gap fillers that can be used even in complex shapes has increased.
[0004] In addition, in recent cars, fuel efficiency has become one of the important differentiating factors, and the weight of the car body is required to be reduced as much as possible. This is also true for on-board electrical components, and development of lightweight and miniaturized components is being promoted. However, if electrical components are miniaturized, the amount of heat generated per unit volume, i.e., the heat density, increases. Therefore, the heat dissipation gap filler is required to be reliable enough to be used for a long time without reducing performance such as thermal conductivity.
[0005] Various studies have been conducted on the reliability of thermally conductive compositions. For example, Patent Document 1 discloses a thermally conductive silicone gel composition, characterized in that: (A) an organopolysiloxane having two alkenyl groups in one molecule, (B) an organohydrogenpolysiloxane having two Si-H groups in one molecule, (C) an organohydrogenpolysiloxane having three or more Si-H groups in one molecule, (D) at least one compound selected from the following (D1) and (D2), (D1) an organopolysiloxane having one alkenyl group in one molecule, (D2) an organopolysiloxane having one Si-H group in one molecule, (E) a platinum catalyst, and (F) a thermally conductive filler, wherein the composition containing 100 to 600% by volume is cured when the total amount of the above (A) to (E) is 100% by volume.
[0006] Patent Document 1 describes that by adjusting the molecular weight of component (D) so as not to increase, it is possible to provide a thermally conductive silicone gel composition that is a gel-like cured product and has low oil precipitation. However, Patent Document 1 assumes that the surface temperature of heat-generating electronic components such as IC packages is about 80°C, and does not mention reliability at higher temperatures.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2021 / 140694 Summary of the invention
[0010] Inventions should solve problems
[0011] However, in recent cars, in order to improve the livability of the interior, it is required to expand the interior space. In the layout research of the body parts, large and heavy trunk parts such as engines or motors are often configured first, and relatively small and light parts such as electrical components sometimes have to be configured in the remaining space. As a result, electrical components are sometimes exposed to high temperature environments above 150°C in the engine room or near the motor, and heat dissipation gap fillers are also used at high temperatures. However, the heat dissipation gap fillers formed by the existing thermally conductive silicone thermally conductive composition will increase in hardness if used for a long time in a high temperature environment above 150°C, causing peeling of the heating element or the heat dissipation element, making it difficult to suppress the increase in thermal resistance.
[0012] In order to improve flexibility, the conventional thermally conductive composition containing organopolysiloxane having alkenyl groups and organohydrogenpolysiloxane having hydrosilyl groups as main components of silicone resin may be prepared by lengthening the molecular chains between crosslinks and reducing the functional group concentration to disperse the crosslinking points.
[0013] However, if the molecular chain between crosslinks is extended, the molecular weight of the silicone resin increases and becomes highly viscous. Silicone resins with large molecular weights have low reactivity, and when the curing reaction proceeds, it is difficult for the thermally conductive composition to diffuse in the solid when it changes from a liquid to a solid. Therefore, the more the reaction of the silicone resin proceeds, the less likely the reactive groups are to contact each other, and eventually unreacted components will remain for a long time. If unreacted components remain, there is a problem of reduced heat resistance in a high temperature environment, such as above 150°C. In this case, reactions from unreacted functional groups, such as crosslinking reactions between hydrosilyl groups, occur, and the hardness of the cured product sometimes increases.
[0014] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a thermally conductive composition capable of obtaining a thermally conductive member with a suppressed increase in hardness even in a high-temperature environment of 150° C. or higher.
[0015] Solution
[0016] As a result of intensive studies, the present inventors have found that an organosilicon compound having a methacryloyl group has a slow addition reaction rate even when the molecular weight is lower than that of an organosilicon compound having an alkenyl group as a main agent, and can solve the above-mentioned problems.
[0017] That is, the present invention provides the following solutions [1] to
[19] .
[0018] [1]. A thermally conductive composition comprising the following components:
[0019] (A) an organopolysiloxane having an alkenyl group,
[0020] (B) an organohydrogenpolysiloxane having a hydrosilyl group,
[0021] (C) Thermally conductive filling materials,
[0022] (D) a polysiloxane compound having a methacryloyl group, and
[0023] (E) a hydrosilylation catalyst,
[0024] The weight average molecular weight M of the component (D) wd Less than the weight average molecular weight M of the component (A) wa .
[0025] [2] A thermally conductive composition comprising the following components:
[0026] (A) an organopolysiloxane having an alkenyl group,
[0027] (B) an organohydrogenpolysiloxane having a hydrosilyl group,
[0028] (C) Thermally conductive filling materials,
[0029] (D) a polysiloxane compound having a methacryloyl group, and
[0030] (E) a hydrosilylation catalyst,
[0031] The composition is composed of a combination of a first agent and a second agent,
[0032] The first agent contains at least one of the components (A) and (D) and the component (E), but does not contain the component (B).
[0033] The second agent contains the component (B) but does not contain the component (E),
[0034] The component (C) is contained in at least one of the first agent and the second agent,
[0035] The weight average molecular weight M of the component (D) wd Less than the weight average molecular weight M of the component (A) wa .
[0036] [3] The thermally conductive composition according to [1] or [2], wherein the weight average molecular weight of the component (D) is M wd and the weight average molecular weight M of the component (A) wa Satisfies the following formula (1):
[0037] M wd ×2.3≤M wa (1).
[0038] [4] The thermally conductive composition according to any one of [1] to [3], wherein the Me content and the Vi content satisfy the following formula (2) and formula (3) on a molar basis, wherein the Me content represents the content of methacryloyl groups, and the Vi content represents the content of alkenyl groups,
[0039] 0.10≤α≤0.60 (2)
[0040] α=Me content / (Me content+Vi content) (3).
[0041] [5] The thermally conductive composition according to any one of [1] to [4], wherein the content H of the hydrosilyl groups and the content Vi of the alkenyl groups satisfy the following formula (4) on a molar basis:
[0042] 0.8≤H / Vi≤1.5 (4).
[0043] [6] The thermally conductive composition according to any one of [1] to [5], wherein the content H of the hydrosilyl groups, the content Vi of the alkenyl groups and the content Me of the methacryloyl groups satisfy the following formula (5) on a molar basis:
[0044] 0.4≤H / (Vi+Me)≤1.2 (5).
[0045] [7] The thermally conductive composition according to any one of [1] to [6], wherein the relationship between the E-type hardness E1 after the thermally conductive composition is left at 25°C for 24 hours and the E-type hardness E2 after the thermally conductive composition is left at 25°C for 24 hours and then left at 150°C for 250 hours satisfies the following formula (6):
[0046] E2 / E1≤1.5 (6).
[0047] [8] The thermally conductive composition according to any one of [1] to [7], further comprising (F) an organopolysiloxane having no addition reactive group.
[0048] [9] The thermally conductive composition according to any one of [1] to [8], having a viscosity of 10 to 1000 Pa·s at a temperature of 25° C. and a shear rate of 3.16, wherein the unit of the shear rate is 1 / s.
[0049]
[10] . The thermally conductive composition according to any one of [1] to [9], wherein the component (C) contains aluminum oxide.
[0050]
[11] . First dose,
[0051] The thermally conductive composition is used as a thermally conductive composition containing the following components by mixing with the second component:
[0052] (A) an organopolysiloxane having an alkenyl group,
[0053] (B) an organohydrogenpolysiloxane having a hydrosilyl group,
[0054] (C) Thermally conductive filling materials,
[0055] (D) a polysiloxane compound having a methacryloyl group, and
[0056] (E) a hydrosilylation catalyst,
[0057] The first agent contains at least one of the components (A) and (D) and the component (E), but does not contain the component (B).
[0058] By combining with the second agent, the weight average molecular weight M of the component (D) is wd Less than the weight average molecular weight M of the component (A) wa .
[0059]
[12] . Second dose,
[0060] The thermally conductive composition is used as a thermally conductive composition containing the following ingredients by mixing with the first agent:
[0061] (A) an organopolysiloxane having an alkenyl group,
[0062] (B) an organohydrogenpolysiloxane having a hydrosilyl group,
[0063] (C) Thermally conductive filling materials,
[0064] (D) a polysiloxane compound having a methacryloyl group, and
[0065] (E) a hydrosilylation catalyst,
[0066] The second agent contains the component (B) but does not contain the component (E),
[0067] By combining with the first agent, the weight average molecular weight M of the component (D) is wd Less than the weight average molecular weight M of the component (A) wa .
[0068]
[13] . A thermally conductive component obtained by curing the thermally conductive composition according to any one of [1] to
[10] .
[0069]
[14] An electrical component, wherein the thermally conductive component is formed by curing the thermally conductive composition according to any one of [1] to
[10] and is interposed between a heat generating body and a heat dissipating body.
[0070]
[15] . In the electrical component described in
[14] , the heating element is arranged at least one of inside the engine room and near the motor.
[0071]
[16] The electrical component described in
[14] or
[15] is exposed to an environment of 150°C or above.
[0072]
[17] . A method of use, wherein a thermally conductive component formed by curing the thermally conductive composition according to any one of [1] to
[10] is interposed between a heat generating body and a heat dissipating body.
[0073]
[18] . The method of use as described in
[17] , wherein the heating element is a semiconductor element.
[0074]
[19] . The method of use as described in
[17] or
[18] , wherein the heating element generates heat to 150°C or above.
[0075] Effects of the Invention
[0076] According to the present invention, it is possible to provide a thermally conductive composition capable of obtaining a thermally conductive member in which an increase in hardness is suppressed even in a high-temperature environment of 150° C. or higher. DETAILED DESCRIPTION
[0077] [Thermal conductive composition]
[0078] Hereinafter, the thermally conductive composition of the present invention will be described in detail.
[0079] The thermally conductive composition of the present invention comprises the following components (A) to (E). Components (A) to (E) are described in detail below.
[0080] <(A)Component>
[0081] The component (A) is an organopolysiloxane having an alkenyl group. The thermally conductive composition can undergo an addition reaction with the organohydrogenpolysiloxane described later to form a cured product having an appropriate hardness by containing the component (A). The component (A) can also be a mixture of a plurality of organopolysiloxanes having an alkenyl group. In addition, the organopolysiloxane having an alkenyl group used as the component (A) can be linear or branched, or a mixture of linear and branched, but is preferably linear.
[0082] The alkenyl group in the component (A) may be contained at either the terminal or in the middle of the molecular chain of the polysiloxane structure of the component (A), or may be contained at both the terminal and in the middle. However, it is preferably contained at least at the terminal, more preferably contained at both terminals of the molecular chain composed of the polysiloxane structure, and more preferably contained only at both terminals.
[0083] The alkenyl group is not particularly limited, and examples thereof include alkenyl groups having 2 to 8 carbon atoms, such as vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, etc. Among them, vinyl is preferred from the viewpoint of ease of synthesis and reactivity. In addition, the alkenyl group may be an alkenyl group directly bonded to a silicon atom.
[0084] The number of alkenyl groups in one molecule of the component (A) may be 1 or more, preferably 2 or more, more preferably 2 to 4, further preferably 2 to 3, further preferably 2.
[0085] In addition, component (A) may contain a plurality of components having different numbers of alkenyl groups in the organopolysiloxane having alkenyl groups, but from the viewpoint of imparting a certain degree of curability to the thermally conductive composition, the organopolysiloxane contained as the main component preferably has 2 or more alkenyl groups, more preferably 2 to 4, further preferably 2 to 3, and further preferably 2. In addition, the so-called main component refers to the component with the highest content ratio among the organopolysiloxanes in component (A). In addition, the organopolysiloxane having 2 or more alkenyl groups may account for, for example, 50 to 100% by mass, preferably 70 to 100% by mass, in component (A).
[0086] In addition, in this specification, the range expressed by "to" means a range from more than the prescribed numerical value described before and after "to" to less than the prescribed numerical value.
[0087] As other groups bonded to silicon atoms other than alkenyl, alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and dodecyl, aryl groups such as phenyl, aralkyl groups such as 2-phenylethyl and 2-phenylpropyl, and substituted hydrocarbon groups such as chloromethyl and 3,3,3-trifluoropropyl can be cited as specific examples. Among them, methyl is preferred from the viewpoint of ease of synthesis. In addition, among other groups bonded to silicon atoms, preferably 80 mol% or more are methyl, more preferably 90 mol% or more are methyl, and further preferably 100 mol% are methyl. In addition, other groups bonded to silicon atoms in component (A) do not have hydrogen atoms, that is, component (A) does not contain hydrosilyl groups.
[0088] (A) The organopolysiloxane of the component may be used alone or in combination of two or more.
[0089] In the thermally conductive composition of the present invention, the weight average molecular weight M of the component (A) iswa As described below, as long as the weight average molecular weight M of the component (D) is greater than wd However, from the viewpoint of easily suppressing the hardness increase of the cured product, preventing the crosslinking density in the cured product from being too high, and easily maintaining the flexibility after curing, it is preferably 12000 or more, more preferably 15000 or more, and further preferably 18000 or more. In addition, from the viewpoint of preventing the thermally conductive composition from becoming high-viscosity or imparting a certain degree of reactivity, M wa It is preferably 35,000 or less, more preferably 32,000 or less, and still more preferably 27,000 or less.
[0090] In addition, the weight average molecular weight M of the component (A) is preferably 0.1-0.25 W, which is preferably 0.1-0.25 W, from the viewpoints of easily suppressing the hardness increase of the cured product, preventing the crosslinking density in the cured product from being too high, maintaining the flexibility after curing, and preventing the thermally conductive composition from becoming highly viscous and imparting a certain degree of reactivity. wa It is preferably 12,000 to 35,000, more preferably 15,000 to 32,000, and still more preferably 18,000 to 27,000.
[0091] Here, the weight average molecular weight M of component (A) is wa This refers to the weight average molecular weight of all (A) components contained in the thermal conductivity composition. The same applies to the (D) component described later.
[0092] The viscosity of the component (A) at 25° C. is not particularly limited, and is, for example, 80 to 5000 mPa·s, preferably 150 to 2500 mPa·s, more preferably 200 to 1500 mPa·s, and still more preferably 250 to 800 mPa·s.
[0093] In addition, component (A) is sometimes mixed as a mixture with component (B) described later, and the viscosity of the mixture of components (A) and (B) at 25°C is, for example, 80 to 5000 mPa·s, preferably 150 to 2500 mPa·s, more preferably 200 to 1500 mPa·s, and even more preferably 250 to 800 mPa·s.
[0094] By setting the viscosity of component (A) or the mixture of components (A) and (B) to be above the above lower limit, it is possible to prevent the crosslinking density in the cured product from being too high, thereby making it easy to maintain the softness after curing. In addition, by setting it to be below the above upper limit, it is possible to prevent the thermally conductive composition from becoming high viscosity. Furthermore, by setting the viscosity within the above range, it is easy to make the reactivity of component (A) or components (A) and (B) appropriate.
[0095] In the two-component thermally conductive composition, the viscosity of the component (A) mixed in the first component at 25°C can be adjusted to the above viscosity range, and the viscosity of the mixture of the component (A) and the component (B) mixed in the second component at 25°C can be adjusted to the above viscosity range.
[0096] The content of the component (A) is not particularly limited, and is, for example, 20 to 70% by mass, preferably 25 to 60% by mass, and more preferably 30 to 50% by mass relative to the total amount of the organopolysiloxane contained in the thermally conductive composition. The organopolysiloxane contained in the total amount of the organopolysiloxane is the sum of the component (A), the component (B), and the component (D) that contribute to the addition reaction, and the component (F) that does not participate in the addition reaction.
[0097] <(B) Ingredient>
[0098] The component (B) is an organohydrogenpolysiloxane having a hydrosilyl group. The thermal conductive composition contains the component (B), and the component (B) undergoes an addition reaction with the components (A) and (D), thereby forming a cured product having an appropriate hardness.
[0099] The component (B) may be linear or branched, or a mixture of linear and branched, preferably linear. In the component (B), the hydrosilyl group may be contained at the end of the molecular chain of the polysiloxane structure or in the middle of the molecular chain, or may be contained at both the end and the middle, but preferably at least at the end, and more preferably at both ends of the molecular chain of the polysiloxane structure.
[0100] The number of the hydrosilyl groups in one molecule of the component (B) is not particularly limited, and may be 1 or more, preferably 2 or more, more preferably 2 to 25, and still more preferably 2 to 20.
[0101] As component (B), a component (B-1) having two hydrosilyl groups and a component (B-2) having three or more hydrosilyl groups may be used in combination. There is no particular limitation on the component having two hydrosilyl groups, and for example, it is preferably a linear component having hydrosilyl groups at both ends of the molecular chain of the polysiloxane structure. In addition, for the component having three or more hydrosilyl groups, the number of hydrosilyl groups in one molecule is preferably 3 to 25, and more preferably 3 to 20.
[0102] In the (B) component, as other groups bonded to silicon atoms other than the hydrosilyl group, alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and dodecyl, aryl groups such as phenyl, aralkyl groups such as 2-phenylethyl and 2-phenylpropyl, and substituted hydrocarbon groups such as chloromethyl and 3,3,3-trifluoropropyl can be cited as specific examples. Among them, from the viewpoint of ease of synthesis, methyl is preferred. In addition, among other groups bonded to silicon atoms, preferably 80 mol% or more are methyl, more preferably 90 mol% or more are methyl, and further preferably 100 mol% are methyl. In addition, the (B) component does not have an alkenyl group as other groups bonded to silicon atoms, that is, it is better that the (B) component does not contain an alkenyl group.
[0103] (B) The organopolysiloxane of the component may be used alone or in combination of two or more.
[0104] The lower limit of the viscosity of the component (B) at 25° C. is not particularly limited, but is, for example, 10 mPa·s or more, preferably 40 mPa·s or more, and more preferably 80 mPa·s or more.
[0105] The upper limit of the viscosity of the component (B) at 25° C. is not particularly limited, but is, for example, 2000 mPa·s or less, preferably 1500 mPa·s or less, and more preferably 1200 mPa·s or less.
[0106] In addition, the viscosity of component (B) at 25°C is not particularly limited, for example, 10 to 2000 mPa·s, preferably 40 to 1500 mPa·s, and more preferably 80 to 1200 mPa·s. By making the viscosity of component (B) above the above lower limit, the crosslinking density can be prevented from becoming high, and the flexibility after curing can be easily improved. In addition, the reactivity is prevented from becoming too fast, and the addition reaction can be easily carried out appropriately. In addition, by making the viscosity of component (B) below the above upper limit, the reactivity can be prevented from decreasing or the thermally conductive composition from becoming highly viscous. Furthermore, by making the viscosity within the above range, the reactivity of component (B) can be easily made appropriate.
[0107] The content of the component (B) can be appropriately selected so that the content ratio H / Vi described later can be adjusted to a predetermined range. The content is not particularly limited, but is, for example, 3 to 35% by mass, preferably 5 to 30% by mass, and more preferably 8 to 25% by mass, relative to the total amount of the organopolysiloxane contained in the thermally conductive composition.
[0108] <(C) Ingredients>
[0109] Component (C) is a thermally conductive filler. The thermally conductive composition of the present invention contains a thermally conductive filler, thereby improving the thermal conductivity of the thermally conductive composition and a cured product (thermally conductive member) obtained by curing the thermally conductive composition.
[0110] Examples of the thermally conductive filler include metals, metal oxides, metal nitrides, metal hydroxides, carbon materials, oxides other than metals, nitrides, carbides, etc. Examples of the shape of the thermally conductive filler include spherical shapes and irregular powders.
[0111] Among the thermally conductive filling materials, as metals, aluminum, copper, nickel, etc. can be listed. As metal oxides, aluminum oxide represented by aluminum oxide, magnesium oxide, zinc oxide, etc. can be listed. As metal nitrides, aluminum nitride, etc. can be exemplified. As metal hydroxides, aluminum hydroxide can be listed. In addition, as carbon materials, spherical graphite, diamond, etc. can be listed. As oxides, nitrides, and carbides other than metals, quartz, boron nitride, silicon carbide, etc. can be listed. Among them, as thermally conductive filling materials, from the viewpoint of improving thermal conductivity, metal oxides, metal nitrides, and carbon materials are preferred, and metal oxides are more preferred. In addition, specifically, aluminum oxide, magnesium oxide, aluminum nitride, diamond are preferred, and aluminum oxide is further preferred.
[0112] These thermally conductive fillers may be used alone or in combination of two or more. For example, from the viewpoint of improving thermal conductivity, it is preferred to use at least one of diamond, magnesium oxide, and aluminum nitride and aluminum oxide together. In addition, from the viewpoint of balancing thermal conductivity and flame retardancy, it is preferred to use aluminum oxide and aluminum hydroxide together.
[0113] The lower limit of the average particle size of the thermally conductive filler is not particularly limited, but from the viewpoint of improving thermal conductivity, it is preferably 0.1 μm or more, more preferably 0.3 μm or more, and further preferably 0.5 μm or more. The upper limit of the average particle size of the thermally conductive filler is not particularly limited, but from the viewpoint of improving the fluidity of the thermally conductive composition, it is preferably 200 μm or less, more preferably 100 μm or less, and further preferably 70 μm or less.
[0114] The average particle size of the thermally conductive filler is not particularly limited, but in order to achieve both the above-mentioned viewpoints, it is preferably 0.1 to 200 μm, more preferably 0.3 to 100 μm, and even more preferably 0.5 to 70 μm.
[0115] As the thermally conductive filler, it is preferred to use a small-particle thermally conductive filler having an average particle size of 0.1 μm to 5 μm and a large-particle thermally conductive filler having an average particle size of more than 5 μm and less than 200 μm. By using thermally conductive fillers having different average particle sizes, the filling rate can be increased. In addition, the average particle size refers to the particle size (D50) when the volume accumulation is 50% in the particle size distribution of the thermally conductive filler obtained by the laser diffraction scattering method.
[0116] The lower limit of the content of the thermally conductive filler in the thermally conductive composition is preferably 150 parts by mass or more, more preferably 500 parts by mass or more, further preferably 1000 parts by mass or more, and further preferably 1500 parts by mass or more, relative to 100 parts by mass of the organopolysiloxane contained in the thermally conductive composition.
[0117] On the other hand, the upper limit of the content of the thermally conductive filler in the thermally conductive composition is preferably 4000 parts by mass or less, more preferably 3500 parts by mass or less, further preferably 3200 parts by mass or less, and further preferably 3000 parts by mass or less, relative to 100 parts by mass of the organopolysiloxane contained in the thermally conductive composition.
[0118] The content of the thermally conductive filler in the thermally conductive composition is preferably 150 to 4000 parts by mass, more preferably 500 to 3500 parts by mass, further preferably 1000 to 3200 parts by mass, further preferably 1500 to 3000 parts by mass, based on 100 parts by mass of the organopolysiloxane contained in the thermally conductive composition.
[0119] When the total amount of the thermally conductive composition is 100 volume %, the lower limit of the volume-based content of the thermally conductive filler is preferably 50 volume % or more, more preferably 70 volume % or more, further preferably 75 volume % or more, further preferably 80 volume % or more.
[0120] When the total amount of the thermally conductive composition is 100 volume %, the upper limit of the volume-based content of the thermally conductive filler is preferably 95 volume % or less, more preferably 93 volume % or less, further preferably 92 volume % or less, and further preferably 90 volume % or less.
[0121] The volume-based content of the thermally conductive filler is preferably 50 to 95 vol%, more preferably 70 to 93 vol%, further preferably 75 to 92 vol%, and even more preferably 80 to 90 vol%, when the total amount of the thermally conductive composition is 100 vol%.
[0122] By making the content of the thermally conductive filler greater than the above lower limit, a certain thermal conductivity can be imparted to the thermally conductive composition and its cured product. By making the content of the thermally conductive filler less than the above upper limit, the thermally conductive filler can be appropriately dispersed. In addition, the viscosity of the thermally conductive composition can be prevented from becoming higher than necessary. In addition, by further setting the content of the thermally conductive filler to the range of the above lower limit to the upper limit, the viewpoint of being able to impart a certain thermal conductivity to the thermally conductive composition and its cured product and the viewpoint of being able to appropriately disperse the thermally conductive filler, and the viscosity of the thermally conductive composition can be prevented from becoming higher than necessary can be taken into account.
[0123] <(D) Ingredient>
[0124] The component (D) is a polysiloxane compound having a methacryloyl group. In the thermally conductive composition of the present invention, the weight average molecular weight M of the component (D) is wd Less than the weight average molecular weight M of component (A) wa In the present invention, the thermally conductive composition contains a weight average molecular weight M wd The weight average molecular weight M of component (A) wa The (D) component is small, thereby suppressing the hardness increase even in a high temperature environment of 150°C or more. If the hardness increase in a high temperature environment is suppressed, the long-term heat resistance is good and the flexibility can be maintained. For example, it is difficult to peel off the heating element or the heat sink, and it is easy to maintain them in a fixed state for a long time. In addition, the (D) component reacts with the (B) component during curing, so precipitation after curing can also be prevented.
[0125] Although the mechanism of suppressing the increase in hardness in a high-temperature environment is not certain, it is presumed as follows.
[0126] In the curing process of the thermally conductive composition of the present invention, in the first half of the process, the hydrosilyl group in the component (B) reacts preferentially with the alkenyl group in the component (A) because the addition reaction rate of the alkenyl group is faster than that of the methacryloyl group. Then, when the crosslinking structure is gradually formed by the components (A) and (B) through the addition reaction, the components (A) and (B) are difficult to diffuse or move in the composition, resulting in the alkenyl group in the component (A) and the hydrosilyl group in the component (B) that have not reacted completely (hereinafter also referred to as "unreacted hydrosilyl group") remaining. Then, in the second half of the process, the methacryloyl group in the component (D) reacts with the hydrosilyl group in the component (B) that has not reacted completely with the alkenyl group in the component (A) (hereinafter also referred to as "unreacted hydrosilyl group"). The thermally conductive composition of the present invention contains a component (D) having a smaller weight average molecular weight than the component (A). Therefore, even in the second half of the curing process when the components (A) and (B) are forming a crosslinked structure, the component (D) easily diffuses or moves in the crosslinked structure due to its small weight average molecular weight, and thus the methacryloyl group of the component (D) and the unreacted hydrosilyl group react easily. Therefore, the amount of unreacted hydrosilyl groups remaining in the thermally conductive composition can be reduced, and even when the composition is used in an environment of 150° C. or higher after curing, the hardness of the cured product can be suppressed from increasing.
[0127] In addition, the hardness of the cured product formed in the above curing process is substantially determined by the cross-linked structure formed by the reaction of the alkenyl group in the component (A) and the hydrosilyl group in the component (B). Therefore, the effect of the reaction of the methacryloyl group in the component (D) and the hydrosilyl group in the component (B) on the hardness of the cured product is limited. Therefore, even if the content of the component (D) increases or decreases, the hardness of the cured product is less likely to change significantly compared to the increase or decrease rate.
[0128] M wa and M wd It is preferable to satisfy the following formula (1).
[0129] M wd ×2.3 ≤ M wa (1)
[0130] By making M wa and M wd Satisfying the formula shown in the above (1) can improve the reactivity of the component (D) with the unreacted hydrosilyl group, and can suppress the hardness increase of the cured product of the thermally conductive composition in a high temperature environment of 150° C. or higher. From the viewpoint of more effectively suppressing the hardness increase of the cured product of the thermally conductive composition, M wa and M wd It is more preferable to satisfy the following formula (1-A), and it is even more preferable to satisfy the formula (1-B).
[0131] M wd ×2.5≤M wa (1-A)
[0132] M wd ×3.0≤M wa (1-B)
[0133] In addition, M wa and M wd The upper limit of the difference is not particularly limited, but by making their difference below a certain value, the weight average molecular weights of components (A) and (D) are adjusted respectively, so as to make their reactivity with the hydrosilyl group in component (B) appropriate. In the formula (1-C) shown below, preferably t is 30, and more preferably t is 10.
[0134] M wa ≤M wd ×t(1-C)
[0135] In the case where the thermally conductive composition is a two-component thermally conductive composition composed of a combination of a first component and a second component described below, the first component and the second component are mixed together to form a thermally conductive composition having a total volume of 100 wt %. wa and M wd The ratio satisfies the above relationship.
[0136] As the polysiloxane compound used as the component (D), an organopolysiloxane is used. The organopolysiloxane of the component (D) may be linear or branched, or a mixture of linear and branched ones, but is preferably linear.
[0137] The methacryloyl group may be contained at the end of the molecular chain of the polysiloxane structure or in the middle of the molecular chain, preferably at the end, and more preferably at one end of the molecular chain of the polysiloxane structure. The component (D) may have one or more methacryloyl groups in the molecule, but preferably has one methacryloyl group from the viewpoint of obtaining a cured product having excellent heat resistance.
[0138] The methacryloyl group may be a methacryloyl group directly bonded to a silicon atom, but may also be bonded to a silicon atom via any divalent group (for example, a divalent saturated aliphatic hydrocarbon group, a group represented by -XO- (wherein X is a divalent saturated aliphatic hydrocarbon group, and the divalent saturated aliphatic hydrocarbon group has, for example, 1 to 18 carbon atoms, preferably 1 to 6, and more preferably 2 to 4 carbon atoms. In addition, -XO- is preferably bonded to the methacryloyl group by an oxygen atom)) or an oxygen atom.
[0139] In the component (D), other groups bonded to silicon atoms are the same as those listed in the component (A), but methyl groups are preferred from the viewpoint of ease of synthesis. In addition, among other groups bonded to silicon atoms, preferably 80 mol% or more are methyl groups, more preferably 90 mol% or more are methyl groups, and further preferably 100 mol% are methyl groups. In addition, the component (D) does not have a hydrogen atom as other groups bonded to silicon atoms, that is, the component (D) preferably does not contain a hydrosilyl group.
[0140] (D) The organopolysiloxane of the component may be used alone or in combination of two or more.
[0141] (D) Weight average molecular weight M of component wd Smaller than the weight average molecular weight M of the above-mentioned component (A) wa , preferably satisfying the formula shown in (1) above. wd It is preferably 15000 or less, more preferably 12000 or less, and still more preferably 7000 or less. wd When the content is below the upper limit, the reaction with the hydrosilyl group remaining in the thermally conductive composition can be promoted, and the hardness increase of the cured product can be suppressed. In addition, the thermally conductive composition can be prevented from becoming highly viscous.
[0142] On the other hand, for M wd The lower limit of is not particularly limited, but is preferably 800 or more, more preferably 1500 or more, and further preferably 3000 or more, from the viewpoint of reducing the viscosity of the thermally conductive composition.
[0143] In addition, from the viewpoint of promoting the reaction with the hydrosilyl group remaining in the thermally conductive composition, suppressing the hardness increase of the cured product, and reducing the viscosity of the thermally conductive composition, M wd It is preferably 800 to 15,000, more preferably 1,500 to 12,000, and more preferably 3,000 to 7,000.
[0144] The viscosity of the component (D) at 25° C. is not particularly limited, but is, for example, 10 to 2000 mPa·s, preferably 50 to 1000 mPa·s, and more preferably 80 to 600 mPa·s.
[0145] By making the viscosity of component (D) above the above lower limit, the crosslinking density in the cured product can be easily reduced, and the flexibility after curing can be easily improved. In addition, by setting it below the above upper limit, the thermally conductive composition can be prevented from becoming high viscosity. In addition, by adjusting the viscosity of component (D) within the above range, the reactivity of component (D) can be adjusted to an appropriate viscosity.
[0146] The content of the component (D) can be appropriately selected so that the content ratio H / Vi described later can be adjusted to a desired range, and is not particularly limited. It is, for example, 1% by mass or more, preferably 2% by mass or more, more preferably 3% by mass or more, and further preferably 4% by mass or more, relative to the total amount of the organopolysiloxane contained in the thermally conductive composition. It is, for example, 55% by mass or less, preferably 50% by mass or less, more preferably 45% by mass or less, and further preferably 30% by mass or less.
[0147] The content of the component (D) is not particularly limited, but is, for example, 1 to 55 mass %, preferably 2 to 50 mass %, more preferably 3 to 45 mass %, and further preferably 4 to 30 mass % based on the total amount of the organopolysiloxane contained in the thermally conductive composition.
[0148] <(E) Ingredient>
[0149] The thermally conductive composition of the present invention contains a hydrosilylation catalyst as component (E). The thermally conductive composition of the present invention can promote the addition reaction of the organopolysiloxane containing alkenyl groups and the organohydrogenpolysiloxane by containing a hydrosilylation catalyst, so that the thermally conductive composition is properly cured. The hydrosilylation catalyst is not particularly limited, and examples thereof include chloroplatinic acid, complexes of chloroplatinic acid and olefins, vinyl siloxanes or acetylene compounds, etc. The content of the platinum-based curing catalyst in the thermally conductive composition is not particularly limited as long as it contains an amount that can promote the addition reaction, and is, for example, 0.001 to 1 part by mass, preferably 0.005 to 0.5 parts by mass, relative to 100 parts by mass of the organopolysiloxane contained in the thermally conductive composition.
[0150] <(F)Component>
[0151] The thermally conductive composition of the present invention also preferably contains an organopolysiloxane having no addition reaction group as the component (F). By containing the component (F), the thermally conductive composition of the present invention can improve flexibility in the cured product without causing more than a certain amount of components to be wrapped in the cross-linked structure. In addition, the viscosity of the thermally conductive composition can be easily reduced, and the operability can be easily improved. In addition, the addition reaction group refers to a functional group that reacts through an addition reaction, and representative examples thereof include alkenyl, methacryloyl, acryloyl, and hydrosilyl.
[0152] As the component (F), there can be listed (F-1) silicone oil and (F-2) organopolysiloxane having at least one alkoxy group. The component (F) may contain any one of the components (F-1) and (F-2), but preferably contains at least the component (F-2). By containing the component (F-2), it is easy to further reduce the viscosity of the thermally conductive composition. When containing the component (F-2), the thermally conductive composition may also contain the component (F-1).
[0153] As (F-1) silicone oil, in addition to straight-chain silicone oils such as dimethyl silicone oil and methylphenyl silicone oil, non-reactive modified silicone oils having a main chain having a polysiloxane structure, a side chain combined with the main chain, or a terminal of the main chain, etc. can also be cited. Non-reactive organic groups refer to organic groups that do not have addition reaction groups. As non-reactive modified silicone oils, for example, polyether-modified silicone oils, aralkyl-modified silicone oils, fluoroalkyl-modified silicone oils, long-chain alkyl-modified silicone oils, higher fatty acid ester-modified silicone oils, higher fatty acid amide-modified silicone oils, and phenyl-modified silicone oils can be cited. Among the above, straight-chain silicone oils are preferred as silicone oils, and dimethyl silicone oil is more preferred among the straight-chain silicone oils.
[0154] The (F-1) silicone oil may be used alone or in combination of two or more.
[0155] The component (F-2) may be linear or branched, or a mixture of linear and branched, but is preferably linear. In addition, the component (F-2) may be any organic polysiloxane having at least one alkoxy group, preferably an organic polysiloxane having at least one alkoxy group at the molecular chain end of the polysiloxane structure, and more preferably an organic polysiloxane having at least one alkoxy group at only one end. It is presumed that the component (F-2) easily reacts or interacts with functional groups present on the surface of the thermally conductive filler material by having an alkoxy group, especially an alkoxy group at the end, and also promotes each other with the case of having a polysiloxane structure, thereby easily reducing the friction of the filler material and easily reducing the viscosity of the thermally conductive composition.
[0156] Specifically, the component (F-2) preferably has a structure represented by the following formula (X).
[0157]
[0158] (In formula (X), R 1 , R 2 , R 4 , R 5 are independently saturated hydrocarbon groups, R 3 is an oxygen atom or a divalent hydrocarbon group, n is an integer of 15 to 315, and m is an integer of 0 to 2)
[0159] By using the component (F-2) having a structure represented by the formula (X), the viscosity-lowering effect of the thermally conductive composition is further increased.
[0160] In formula (X), R 1 , R 2 , R 4 , R 5 Each independently represents a saturated hydrocarbon group. Examples of the saturated hydrocarbon group include alkyl groups such as linear alkyl groups, branched alkyl groups, and cyclic alkyl groups, aryl groups, aralkyl groups, and halogenated alkyl groups.
[0161] Examples of the linear alkyl group include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, etc. Examples of the branched alkyl group include isopropyl, tert-butyl, isobutyl, 2-methylundecyl, 1-hexylheptyl, etc. Examples of the cyclic alkyl group include cyclopentyl, cyclohexyl, cyclododecyl, etc.
[0162] Examples of the aryl group include phenyl, tolyl, and xylyl. Examples of the aralkyl group include benzyl, phenethyl, and 2-(2,4,6-trimethylphenyl)propyl. Examples of the halogenated alkyl group include 3,3,3-trifluoropropyl and 3-chloropropyl.
[0163] From the viewpoint of improving the viscosity-lowering effect, R in formula (X) 1 ~R 5 , m, and n are preferably as follows.
[0164] R in formula (X) 1 An alkyl group having 1 to 8 carbon atoms is preferred, an alkyl group having 2 to 6 carbon atoms is more preferred, and a butyl group is particularly preferred.
[0165] R in formula (X) 2 , R 4 , R 5 Each of them independently is preferably an alkyl group having 1 to 8 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and particularly preferably a methyl group.
[0166] R in formula (X) 3 is an oxygen atom or a divalent hydrocarbon group, preferably a divalent hydrocarbon group. Examples of the divalent hydrocarbon group include methylene, ethylene, propylene, butylene, and methylethylene, among which ethylene is preferred.
[0167] n in formula (X) is an integer of 15 to 315, preferably an integer of 18 to 280, more preferably an integer of 20 to 220. m in formula (X) is an integer of 0 to 2, preferably 0 or 1, more preferably 0. Therefore, the component (F-2) is preferably an organopolysiloxane having a trialkoxysilyl group at one terminal.
[0168] The component (F-2) may be used alone or in combination of two or more.
[0169] The lower limit of the viscosity of the component (F) at 25° C. is not particularly limited, but is, for example, 1 mPa·s or more, preferably 5 mPa·s or more, and more preferably 10 mPa·s or more.
[0170] On the other hand, the upper limit of the viscosity of the component (F) at 25°C is not particularly limited, but is, for example, 800 mPa·s or less, preferably 250 mPa·s or less, and more preferably 150 mPa·s or less.
[0171] In addition, there is no particular limitation on the viscosity of the component (F) at 25°C, and it is, for example, 1 to 800 mPa·s, preferably 5 to 250 mPa·s, and more preferably 10 to 150 mPa·s. By making the viscosity of the component (F) above the above lower limit, it is also easy to prevent precipitation after curing. On the other hand, by making the viscosity of the component (F) below the above upper limit, it is possible to easily form a cured product while reducing the viscosity of the thermally conductive composition without increasing the viscosity of the component (F) itself. In addition, by making the viscosity of the component (F) within the above range, it is also easy to prevent precipitation after curing, and the viscosity of the thermally conductive composition can be effectively reduced by the component (F), while also easily forming a cured product.
[0172] The content of the component (F) in the thermally conductive composition is based on the total amount of the organopolysiloxane contained in the thermally conductive composition, for example, 3% by mass or more, for example, 63% by mass or less. By making the content of the component (F) above the lower limit, it is easy to improve the softness of the cured product obtained from the thermally conductive composition, and it is also easy to reduce the viscosity of the thermally conductive composition by the component (F). In addition, by making the content of the component (F) below the upper limit, it is possible to impart a certain curability to the thermally conductive composition, it is easy to obtain a cured product with desired physical properties, and it is also easy to prevent precipitation after curing. The lower limit of the content of the component (F) in the thermally conductive composition is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. On the other hand, the upper limit of the content of the component (F) in the thermally conductive composition is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 35% by mass or less. The upper limit of the content of the component (F) in the thermally conductive composition is preferably 3 to 63% by mass, more preferably 5 to 50% by mass, further preferably 10 to 40% by mass, and further preferably 15 to 35% by mass.
[0173] As described above, component (F) preferably contains component (F-2). The lower limit of the content of component (F-2) in the thermally conductive composition is preferably 2% by mass or more, more preferably 4% by mass or more, and more preferably 8% by mass or more, based on the total amount of the organopolysiloxane contained in the thermally conductive composition. On the other hand, the upper limit of the content of component (F-2) in the thermally conductive composition is preferably 40% by mass or less, more preferably 30% by mass or less, and more preferably 20% by mass or less. In addition, the content of component (F-2) in the thermally conductive composition is preferably 2 to 40% by mass, more preferably 4 to 30% by mass, and more preferably 8 to 20% by mass.
[0174] The thermally conductive composition containing the component (F-2) in an amount greater than or equal to the above lower limit can more easily reduce the viscosity of the thermally conductive composition by containing the component (F-2) in an amount greater than or equal to a certain amount in the component (F). In addition, by making the component (F) equal to or less than the above upper limit, a certain curability can be imparted to the thermally conductive composition, and a cured product having desired physical properties can be easily obtained, and precipitation after curing can be easily prevented.
[0175] In the thermally conductive composition of the present invention, the lower limit of the total content of the components (A), (B), (D) and (F) is preferably 2% by mass or more relative to the total amount of the thermally conductive composition. In addition, in the thermally conductive composition of the present invention, the upper limit of the total content of the components (A), (B), (D) and (F) is preferably 40% by mass or less relative to the total amount of the thermally conductive composition. By making the total amount of the components (A), (B), (D) and (F) more than a certain amount, these components can properly function as a binder resin, and the thermally conductive filler can be properly retained by these components. In addition, by making the above-mentioned total content less than a certain amount, a large amount of thermally conductive filler can be contained to improve thermal conductivity.
[0176] From the above viewpoints, the lower limit of the total content of the components (A), (B), (D) and (F) is more preferably 3% by mass or more, more preferably 3.5% by mass or more, and more preferably 4% by mass or more, relative to the total amount of the thermally conductive composition. On the other hand, the upper limit of the total content of the components (A), (B), (D) and (F) is more preferably 20% by mass or less, more preferably 15% by mass or less, and more preferably 10% by mass or less, relative to the total amount of the thermally conductive composition. In addition, the total content of the components (A), (B), (D) and (F) is more preferably 3 to 20% by mass, more preferably 3.5 to 15% by mass, and more preferably 4 to 10% by mass, relative to the total amount of the thermally conductive composition.
[0177] The organopolysiloxane in the thermally conductive composition of the present invention may be composed of components (A), (B), (D) or components (A), (B), (D), and (F), but may contain organopolysiloxanes other than components (A), (B), (D), and (F) within a range that does not impair the effects of the present invention. The content of the organopolysiloxane other than components (A), (B), (D), and (F) is, for example, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and most preferably 0% by mass, relative to the total amount of the organopolysiloxane contained in the thermally conductive composition.
[0178] The thermally conductive composition of the present invention may contain various additives. Examples of additives include reaction control agents, dispersants, flame retardants, plasticizers, antioxidants, colorants, and the like. In addition, each additive may be contained in either the first component or the second component of the two-component thermally conductive composition, or may be contained in both. One or more additives may be appropriately selected and used.
[0179] <Alkenyl and Methacryloyl Content>
[0180] The total content of alkenyl groups and methacryloyl groups in the total amount of the organopolysiloxane contained in the thermally conductive composition (hereinafter also referred to as "total Vi+Me content 1") is preferably 0.30 mmol / g or less. By making the total Vi+Me content 1 0.30 mmol / g or less, it is easy to reduce the crosslinking density of the cured product and improve the flexibility. The total Vi+Me content 1 is more preferably 0.25 mmol / g or less, further preferably 0.15 mmol / g or less, and further preferably 0.12 mmol / g or less.
[0181] From the viewpoint of imparting certain curability and appropriate crosslinking density to the thermally conductive composition, the total Vi+Me content 1 is preferably 0.02 mmol / g or more, more preferably 0.04 mmol / g or more, further preferably 0.06 mmol / g or more, and still further preferably 0.08 mmol / g or more.
[0182] From the viewpoint of making the crosslinking density of the cured product moderate and having moderate flexibility, the total Vi+Me content is preferably 0.02 to 0.30 mmol / g, more preferably 0.04 to 0.25 mmol / g, further preferably 0.06 to 0.15 mmol / g, and still further preferably 0.08 to 0.12 mmol / g.
[0183] In the two-component thermally conductive composition, the total Vi+Me content 1 can be measured for each of the first and second components. However, the preferred range of the total Vi+Me content 1 is the value of the first and second components combined.
[0184] The total content of alkenyl and methacryloyl groups in the thermally conductive composition (hereinafter also referred to as "total Vi+Me content 2") is preferably 8.0 μmol / g or less. By setting the total Vi+Me content 2 to 8.0 μmol / g or less, it is easy to reduce the crosslinking density in the cured product and improve the flexibility. The total Vi+Me content 2 is more preferably 7.0 μmol / g or less, more preferably 6.5 μmol / g or less, and even more preferably 6.0 μmol / g or less.
[0185] From the viewpoint of imparting certain curability and appropriate crosslinking density to the thermally conductive composition, the total Vi+Me content 2 is preferably 0.5 μmol / g or more, more preferably 1.0 μmol / g or more, even more preferably 2.0 μmol / g or more, and even more preferably 3.0 μmol / g or more.
[0186] In addition, from the viewpoint of making the crosslinking density in the cured product moderate and imparting moderate flexibility to the cured product, the total Vi+Me content 2 is preferably 0.5 to 8.0 μmol / g, more preferably 1.0 to 7.0 μmol / g, further preferably 2.0 to 6.5 μmol / g, and still more preferably 3.0 to 6.0 μmol / g.
[0187] The content of the alkenyl group and the methacryloyl group described below may be a value calculated from the integrated ratio of the 1H-NMR spectrum measured using an NMR measuring device.
[0188] The content of methacryloyl groups in the total amount of organopolysiloxane contained in the thermally conductive composition (hereinafter also referred to as "Me content 1") is preferably 0.15 mmol / g or less. By making the Me content 1 0.15 mmol / g or less, it is easy to reduce the residual amount of unreacted hydrosilyl groups without containing more than the necessary amount of methacryloyl groups, and suppress the increase in hardness in a high temperature environment after curing. The Me content 1 is more preferably 0.12 mmol / g or less, further preferably 0.08 mmol / g or less, and further preferably 0.05 mmol / g or less.
[0189] From the viewpoint of sufficiently reducing the amount of unreacted hydrosilyl groups remaining in the thermally conductive composition and suppressing an increase in hardness in a high-temperature environment after curing, the Me content 1 is preferably 0.002 mmol / g or more, more preferably 0.004 mmol / g or more, further preferably 0.006 mmol / g or more, and even more preferably 0.008 mmol / g or more.
[0190] In addition, from the viewpoint of easily reducing the residual amount of unreacted hydrosilyl groups without containing more than the necessary amount of methacryloyl groups and suppressing the increase in hardness in a high-temperature environment after curing, the total Me content 1 is preferably 0.002 to 0.15 mmol / g, more preferably 0.004 to 0.12 mmol / g, further preferably 0.006 to 0.08 mmol / g, and further more preferably 0.008 to 0.05 mmol / g.
[0191] In the case of a two-component thermally conductive composition, the total Me content 1 may be measured for each of the first and second components. However, the preferred range of the total Me content 1 is the value of the total of the first and second components.
[0192] The content of methacryloyl groups in the thermally conductive composition (hereinafter also referred to as "Me content 2") is preferably 4.0 μmol / g or less. By setting the Me content 2 to 4.0 μmol / g or less, the amount of unreacted hydrosilyl residues can be reduced without containing more than the necessary amount of methacryloyl groups, and the hardness increase in a high temperature environment after curing can be easily suppressed. The Me content 2 is more preferably 3.5 μmol / g or less, more preferably 3.0 μmol / g or less, and even more preferably 2.5 μmol / g or less.
[0193] From the viewpoint of sufficiently reducing the amount of unreacted hydrosilyl groups remaining in the thermally conductive composition and suppressing an increase in hardness in a high-temperature environment after curing, the Me content 2 is preferably 0.05 μmol / g or more, more preferably 0.1 μmol / g or more, further preferably 0.2 μmol / g or more, and still more preferably 0.3 μmol / g or more.
[0194] In addition, from the viewpoint of not containing more than the necessary amount of methacryloyl groups, reducing the residual amount of unreacted hydrosilyl groups, and easily suppressing the increase in hardness in a high-temperature environment after curing, the total Me content 2 is preferably 0.05 to 4.0 μmol / g, more preferably 0.1 to 3.5 μmol / g, further more preferably 0.2 to 3.0 μmol / g, and still more preferably 0.3 to 2.5 μmol / g.
[0195] In addition, when the total content of alkenyl groups in the total amount of organopolysiloxane contained in the thermally conductive composition is hereinafter referred to as “total Vi content 1”, and when the total content of alkenyl groups in the thermally conductive composition is hereinafter referred to as “total Vi content 2”, the total of “Me content 1” and “total Vi content 1” is “total Vi + Me content 1”, and the total of “Me content 2” and “total Vi content 2” is “total Vi + Me content 2”.
[0196] On a molar basis, it is preferred that the Me content 2 and the total Vi content 2 satisfy the following formulas (2) and (3).
[0197] 0.10≤α≤0.60 (2)
[0198] α = Me content 2 / (total Vi + Me content 2) (3)
[0199] As shown in the above formulas (2) and (3), by making the ratio of the Me content in the total Vi+Me content to a certain amount or more, the amount of unreacted hydrosilyl residues in the thermally conductive composition can be reduced, the crosslinking points can be prevented from becoming too dense, and the hardness increase of the cured product under high temperature environment can be suppressed. The Me content is more preferably 0.15 or more, and more preferably 0.19 or more relative to the total Vi+Me content. In addition, from the viewpoint of reducing the amount of unreacted hydrosilyl residues without containing more than the necessary amount of methacryloyl groups and suppressing the hardness increase under high temperature environment after curing, the Me content is more preferably 0.55 or less, and more preferably 0.50 or less relative to the total Vi+Me content.
[0200] The Me content is more preferably 0.15 to 0.55, and even more preferably 0.19 to 0.50 or more relative to the total Vi+Me content.
[0201] In the thermally conductive composition, the content of alkenyl groups contained in the component (A) having an alkenyl group at only one terminal of the component (A) (i.e., the organopolysiloxane having an alkenyl group) (hereinafter also referred to as "DVi content") is preferably 0.17 or less, more preferably 0.15 or less, further preferably 0.10 or less, and further preferably 0.05 or less relative to the total Vi+Me content from the viewpoint of imparting a certain curability to the thermally conductive composition. From the viewpoint of imparting an appropriate crosslinking structure to the cured product, the lower the DVi content relative to the total Vi+Me content, the better, and it may be 0 or more.
[0202] <Content ratio H / Vi>
[0203] In the thermally conductive composition, the content H of the hydrosilyl groups and the content Vi of the alkenyl groups on a molar basis preferably satisfy the relationship of the following formula (4).
[0204] 0.8≤H / Vi≤1.5 (4)
[0205] Since the thermally conductive composition of the present invention contains component (D), the curability of the thermally conductive composition can be improved by satisfying the relationship of the above formula (4), for example, the thermally conductive composition can be moderately cured at room temperature. In addition, even in a high temperature environment of 150°C or above, the effect of suppressing the hardness increase of the cured product of the thermally conductive composition is also improved. From the viewpoint of reducing the amount of unreacted alkenyl groups, the above H / Vi is more preferably 0.95 or more, and more preferably 1.05 or more. On the other hand, from the viewpoint of reducing the amount of unreacted hydrosilyl groups, the above H / Vi is more preferably 1.40 or less, and more preferably 1.20 or less. In addition, from the viewpoint of reducing the unreacted addition reaction groups to suppress the hardness increase of the cured product of the thermally conductive composition, H / Vi is more preferably 0.95 to 1.40, and more preferably 1.05 to 1.20.
[0206] In addition, regardless of the value of H / Vi, even if H / Vi is 1 or less due to the presence of unreacted alkenyl groups and unreacted hydrosilyl groups remaining in the first half of the curing process, the unreacted hydrosilyl groups can be reacted with the component (D) in the second half of the curing process to suppress the increase in hardness of the cured product of the thermally conductive composition. On the other hand, when the amount of unreacted alkenyl groups remaining is a problem, the amount of unreacted alkenyl groups can be reduced by making the content H of the hydrosilyl groups greater than the content Vi of the alkenyl groups, and further, the unreacted hydrosilyl groups can be reacted with the component (D) in the second half of the curing process to suppress the increase in hardness of the cured product of the thermally conductive composition.
[0207] <Content Ratio H / (Vi+Me)>
[0208] In the thermally conductive composition, the content H of the hydrosilyl groups, the content Vi of the alkenyl groups, and the content Me of the methacryloyl groups on a molar basis preferably satisfy the relationship of the following formula (5).
[0209] 0.4≤H / (Vi+Me)≤1.2 (5)
[0210] The thermally conductive composition of the present invention satisfies the relationship of the above formula (5), so that the curing property of the thermally conductive composition can be improved, for example, the thermally conductive composition can be appropriately cured at room temperature. In addition, even in a high temperature environment of 150° C. or higher, the effect of suppressing the hardness increase of the cured product of the thermally conductive composition is improved.
[0211] From the viewpoint of curability, H / (Vi+Me) is more preferably 0.50 or more, and more preferably 0.55 or more. From the viewpoint of suppressing an increase in hardness, H / (Vi+Me) is more preferably 1.05 or less, and more preferably 0.95 or less.
[0212] Moreover, from the viewpoint of suppressing the increase of curability and hardness, H / (Vi+Me) is more preferably 0.50 to 1.05, and further preferably 0.55 to 0.95.
[0213] The content ratio H / Vi and the content ratio H / (Vi+Me) can be calculated from the functional group amount of each component mixed and the content of each component. The functional group amount of each component mixed can be calculated from the integral ratio of the 1H-NMR spectrum as described above.
[0214] Furthermore, by satisfying the relationship of the following formula (5-2), the thermally conductive composition contains a methacryloyl group, and it is possible to suppress an increase in the hardness of a cured product of the thermally conductive composition in a high temperature environment.
[0215] H / (Vi+Me)<H / Vi (5-2)
[0216] <E type hardness>
[0217] The thermally conductive composition of the present invention preferably has a relationship between the E-type hardness (E1) after being left at 25°C for 24 hours and the E-type hardness (E2) after being left at 25°C for 24 hours and further left at 150°C for 250 hours that satisfies the following formula (6).
[0218] E2 / E1≤1.5 (6)
[0219] If E2 / E1 is less than 1.5, the hardness change after curing will not be too large, so the heat resistance becomes good, for example, it is difficult to peel off the heating element or the heat sink, and it can be stably fixed. From such a viewpoint, E2 / E1 is more preferably less than 1.45. On the other hand, the lower limit of E2 / E1 is not particularly limited, but is, for example, more than 1, preferably more than 1.15 in practicality.
[0220] In addition, the E-type hardness in the present invention is a value measured by an E-type hardness tester in accordance with Japanese Industrial Standards JIS K 6253.
[0221] The E-type hardness (E1) of the thermally conductive composition is preferably 40 or more, more preferably 45 or more, and further preferably 50 or more. The thermally conductive composition can obtain a cured product with a certain hardness by making the E-type hardness (E1) be above a certain value, and only being placed at room temperature. Therefore, for example, in a state after being cured at room temperature, the weight of the components arranged on the upper part of the cured product can be fully supported, and compression in the thickness direction during use can be prevented. In addition, the E-type hardness (E1) of the thermally conductive composition is preferably 65 or less, more preferably 62 or less, and further preferably 60 or less. By making the E-type hardness (E1) be below the above-mentioned upper limit value, the softness of the cured product of the thermally conductive composition can be improved.
[0222] The thermally conductive composition preferably has an E-type hardness (E2) that satisfies the following formula (7-2).
[0223] E2<80 (7-2)
[0224] In addition, the thermally conductive composition may be prepared by mixing the first component and the second component in a two-component thermally conductive composition and then leaving the mixture at 25° C. for 24 hours. The same applies to the measurement of other hardnesses.
[0225] If the above-mentioned E-type hardness (E2) is less than 80, it is easy to maintain the softness of the cured product in an environment of 150°C or above, and it is easy to relax stress such as vibration, so it is difficult to peel off from the heating element or the heat sink. Therefore, if the cured product of the thermally conductive composition is used as a heat dissipation gap filler (thermal conductive component) in an environment of 150°C or above, it is possible to prevent peeling off the heating element or the heat sink, prevent the increase in thermal resistance, and maintain reliability. From the viewpoint of softness and reliability, the E-type hardness (E2) is preferably 75 or less, more preferably 73 or less, and further preferably 70 or less. In addition, if the softness becomes higher, it is easy to exert cushioning properties and can be used well in an environment where vibration occurs.
[0226] In addition, the E-type hardness (E2) is not particularly limited, and is, for example, 30 or more, preferably 40 or more, and more preferably 50 or more. By setting the E-type hardness (E2) to a certain value or more, the softness of the cured product can be easily maintained in an environment of 150° C. or more, and, for example, the weight of a component disposed on the cured product can be sufficiently supported, and the cured product can be prevented from being excessively compressed in the thickness direction during use.
[0227] If the E-type hardness after being placed at 25°C for 24 hours and then at 150°C for 1000 hours is set to E3, the hardness change represented by the value of E3-E2 represents the hardness change when heated at 150°C for a long time. The lower the value of E3-E2, the less the performance change and the better the long-term heat resistance even if it is used for a long time at a temperature above 150°C. From the viewpoint of long-term heat resistance, the hardness change represented by the value of E3-E2 is preferably 6 or less, more preferably 4 or less, and also preferably 2 or less. In addition, there is no particular limitation on the hardness change represented by the value of E3-E2, and it is usually 0 or more.
[0228] <Concentration Ratio of Hydrosilyl Group>
[0229] In the thermally conductive composition according to one embodiment of the present invention, the component (B-1) and the component (B-2) contained in the component (B) are preferably contained so as to satisfy the relationship of the following formula (1-2).
[0230] b1 / (b1+b2)>0.45 (1-2)
[0231] In formula (1-2), b1 is the concentration of the hydrosilyl groups possessed by component (B-1), and b2 is the concentration of the hydrosilyl groups possessed by component (B-2). The concentration of the hydrosilyl groups mentioned here refers to the concentration of the hydrosilyl groups in the thermally conductive composition. However, in the two-component thermally conductive composition described later, the organohydrogenpolysiloxane is not contained in the first agent, but only in the second agent. Therefore, in the two-component thermally conductive composition, it can also be said to refer to the concentration of the hydrosilyl groups in the second agent. That is, component (B-1) and component (B-2) can be contained in the second agent in a manner that satisfies the relationship of formula (1-2).
[0232] In the present composition, when b1 / (b1+b2) is greater than 0.45, the crosslinking points tend to become sparse, and the softness of the cured product tends to be well maintained in an environment of 150°C or above. Therefore, if the cured product of the thermally conductive composition is used as a heat dissipation gap filler in an environment of 150°C or above, it is difficult to peel off the heating element or the heat dissipation element, and it is difficult to cause the unfavorable situation of increased thermal resistance, and the reliability is improved. Furthermore, by improving the softness, for example, in the case of thickening, the cushioning property can be exerted, and it can be used well in an environment where vibration occurs.
[0233] From the viewpoint of making the crosslinking points sparse and improving reliability and flexibility, b1 / (b1+b2) is preferably 0.48 or more, more preferably 0.50 or more, and even more preferably 0.52 or more.
[0234] b1 / (b1+b2) is preferably less than 0.85. By making b1 / (b1+b2) less than 0.85, it is easy to introduce a cross-linked structure with an appropriate cross-linking density in the cured product. Therefore, even if heated at high temperature for a long time, it is easy to maintain the hardness at a certain value, and it is easy to make long-term heat resistance and the like good. From the above viewpoints, b1 / (b1+b2) is more preferably less than 0.75, and further preferably less than 0.70, and further preferably less than 0.63.
[0235] In the present invention, any one of the requirements of the above formula (1-1) and the requirements of the formula (1-2) may be satisfied, but both of them may be satisfied.
[0236] The concentrations of the hydrosilyl groups in the components (B-1) and (B-2) may be values calculated from the integration ratio of the 1H-NMR spectrum measured using an NMR measuring apparatus.
[0237] <Raman intensity ratio p2 / p1>
[0238] In one embodiment of the present invention, the thermally conductive composition preferably has a Raman spectrum at 2160 cm -1 The Raman intensities p1 and 2130 cm -1The Raman intensity p2 satisfies the following relationship (1-1).
[0239] p2 / p1>3.00 (1-1)
[0240] 2160cm in Raman spectrum -1 The Raman intensity p1 is the peak wavelength Raman intensity of the hydrosilyl group contained in the molecular chain of the polysiloxane structure. -1 The Raman intensity p2 is the Raman intensity of the peak wavelength derived from the hydrosilyl groups contained at the molecular chain terminals of the polysiloxane structure. Therefore, p2 / p1 can be said to be an index representing the amount of the terminal hydrosilyl groups relative to the hydrosilyl groups contained in the molecular chain.
[0241] By making p2 / p1 greater than 3.0, the amount of hydrosilyl groups contained at the ends of the molecular chains increases, while the amount of hydrosilyl groups contained in the middle of the molecular chains decreases, so that the crosslinking points tend to become sparse, and the hardness increase of the cured product can be easily suppressed even in an environment of 150°C or above.
[0242] From the viewpoint of making cross-linking points sparse and improving reliability and flexibility, p2 / p1 is preferably 3.10 or more, more preferably 3.20 or more, and still more preferably 3.30 or more.
[0243] In addition, p2 / p1 is preferably less than 5.5. By making p2 / p1 less than 5.5, it is easy to introduce a three-dimensional crosslinked structure with an appropriate crosslinking density in the cured product. Therefore, even if heated at high temperature for a long time, it is easy to maintain the hardness at a certain value, and it is easy to make long-term heat resistance and the like good. From the above viewpoints, p2 / p1 is more preferably less than 4.5, and further preferably less than 4.2, and further preferably less than 4.0.
[0244] <Raman intensity ratio H / (Vi+Me)>
[0245] From the viewpoint of curability, the ratio of the intensity of the peak derived from the hydrosilyl group to the intensity of the peak derived from the alkenyl group and the methacryloyl group in the Raman spectrum (also referred to as "Raman intensity ratio H / (Vi+Me)") is preferably 3.00 or more, more preferably 4.00 or more, and further preferably 5.00 or more. On the other hand, from the viewpoint of suppressing the increase in hardness, the Raman intensity ratio H / (Vi+Me) is preferably 12.00 or less, more preferably 10.00 or less, and further preferably 9.00 or less.
[0246] In addition, the Raman intensity ratio H / (Vi+Me) is preferably 3.00 to 12.00, more preferably 4.00 to 10.00, and further preferably 5.00 to 9.00. By making the Raman intensity ratio H / (Vi+Me) within the above range, the number of hydrosilyl groups and the total number of alkenyl groups and methacryloyl groups are balanced, and it is easy to properly cure the components (A), (B) and (D), for example, even at room temperature. In addition, it is easy to suppress the increase in hardness in a high temperature environment after curing.
[0247] <Raman intensity ratio H / Vi>
[0248] From the viewpoint of reducing the amount of unreacted alkenyl groups, the ratio of the intensity of the peak derived from the hydrosilyl group in the Raman spectrum to the intensity of the peak derived from the alkenyl group (also referred to as "Raman intensity ratio H / Vi") is preferably 7.00 or more, more preferably 8.00 or more, and further preferably 9.50 or more. On the other hand, from the viewpoint of reducing the amount of unreacted hydrosilyl groups, the Raman intensity ratio H / Vi is preferably 14.00 or less, more preferably 12.50 or less, and further preferably 11.00 or less.
[0249] From the viewpoint of reducing unreacted addition reaction groups and suppressing an increase in the hardness of a cured product of the thermally conductive composition, the Raman intensity ratio H / Vi is preferably 7.00 to 14.00, more preferably 8.00 to 12.50, and even more preferably 9.50 to 11.00.
[0250] The Raman intensity ratio H / Vi is a value larger than the Raman intensity ratio H / (Vi+Me).
[0251] In addition, regarding the measurement of Raman spectrum, for the thermally conductive composition, at least the organopolysiloxane and the thermally conductive filler can be separated, and the organopolysiloxane can be subjected to Raman measurement. In this case, components other than the organopolysiloxane can be mixed in the organopolysiloxane as long as they do not affect the measurement. Therefore, the liquid component and the solid component can usually be separated by a centrifuge or the like, and the Raman spectrum of the liquid component can be measured.
[0252] In addition, for a two-component thermally conductive composition, Raman measurements can be performed on the first agent and the second agent respectively to calculate the Raman intensity ratios p2 / p1, H / Vi, and H / (Vi+Me), but the Raman intensity ratio p2 / p1 can be calculated based on the Raman spectrum of the second agent. This is because the organohydrogenpolysiloxane is not contained in the first agent, but only in the second agent. The measurement conditions of the Raman measurement are as follows. In addition, the alkenyl group is typically a vinyl group, and the above Raman intensity ratio H / Vi is typically as described later, and can be obtained by calculating the index of the hydrosilyl / vinyl ratio. The above Raman intensity ratio H / Vi is typically as described later, and can be obtained by calculating the index of the hydrosilyl / (vinyl+methacryloyl) ratio.
[0253] A specific example of Raman measurement when the thermally conductive composition is a two-component type and the alkenyl group is a vinyl group will be described below, but the Raman measurement method is not limited to the following method.
[0254] The first agent and the second agent are separated into liquid components and solid components (thermal conductive filler) using centrifugal separators, respectively. Then, the Raman spectra of the separated liquid components are measured. The Raman spectra are measured under the following conditions, for example.
[0255] Device: inVia Raman microscope QONTOR produced by RENISHAW
[0256] Spectral range: 300~2500cm -1
[0257] Laser wavelength: 532nm, 100mW (dimmed to 10%)
[0258] Grating: 1800line / mm
[0259] Irradiation time: 1.0s
[0260] Total: 100
[0261] Objective lens: 50 times
[0262] The Raman intensity ratio p2 / p1 is obtained from the Raman spectrum of the second agent containing hydrosilyl groups, starting from the wave number 2130 cm -1 The Raman intensity p2 and wave number 2160cm -1 The Raman intensity p1 is estimated.
[0263] The Raman intensity ratio H / Vi (the ratio of the intensity of the peak derived from the hydrosilyl group to the intensity of the peak derived from the alkenyl group) was calculated as follows. That is, for the Raman spectrum of the first agent and the Raman spectrum of the second agent, the wave number 490 cm -1 The peak area C of Si-O-Si shown at wave number 1600 cm-1 The area D of the peak of vinyl and the peak at wave number 2130-2160 cm -1 The peak area of the hydrosilyl group that appears is F. Next, the following calculation is performed based on the area C, and the error of each measured intensity is corrected and normalized.
[0264] Area D / Area C = Area ratio D1
[0265] Area F / Area C=Area ratio F1
[0266] Next, the value obtained by multiplying the area ratio D1 of the first agent by the mass ratio of the liquid component contained in the first agent and the value obtained by multiplying the area ratio D1 and F1 of the second agent by the mass ratio of the liquid component contained in the second agent are added together to estimate D1 and F1 in the thermally conductive composition.
[0267] Then, the index of the hydrosilyl group / vinyl group ratio was calculated by the following formula to obtain the ratio.
[0268] Raman intensity ratio H / Vi = area ratio F1 / area ratio D1
[0269] In addition, the Raman intensity ratio H / (Vi+Me) (the ratio of the intensity of the peak derived from the hydrosilyl group to the intensity of the peak derived from the alkenyl group and the methacryloyl group) was calculated as follows. That is, for the Raman spectrum of the first agent and the Raman spectrum of the second agent, the peak at the wave number 490 cm -1 The area of the Si-O-Si peak C at wave number 1600 cm -1 The area D of the peak of vinyl appears at wave number 1640 cm -1 The peak area E of the methacryloyl group and the peak at wave number 2130-2160 cm -1 The peak area of the hydrosilyl group that appears is F. Next, the following calculation is performed based on the area C, and the error of each measured intensity is corrected and normalized.
[0270] Area D / Area C = Area ratio D1
[0271] Area E / Area C = Area ratio E1
[0272] Area F / Area C=Area ratio F1
[0273] Next, the values obtained by multiplying the area ratio D1, E1 of the first agent by the mass ratio of the liquid component contained in the first agent and the values obtained by multiplying the area ratio D1, E1, F1 of the second agent by the mass ratio of the liquid component contained in the second agent are added together to estimate D1, E1, F1 in the thermally conductive composition.
[0274] Then, the index of the ratio of hydrosilyl group / (vinyl group+methacryloyl group) was calculated by the following formula: Since there is a difference in Raman scattering intensity between vinyl group and methacryloyl group, the ratio was calculated by multiplying by 0.5 as a correction factor.
[0275] Raman intensity ratio H / (Vi+Me)=area ratio F1 / [area ratio D1+(area ratio E1×0.5)]
[0276] Even when the thermally conductive composition has an alkenyl group other than a vinyl group, the peak intensity derived from the alkenyl group other than a vinyl group can be similarly calculated to calculate the Raman intensity ratio H / Vi and the Raman intensity ratio H / (Vi+Me).
[0277] <Two-component thermally conductive composition>
[0278] The thermal conductive composition of the present invention may be a one-component type or a two-component type in which a first component and a second component are combined. The two-component type is preferably used from the viewpoint of storage stability. The two-component type is a thermal conductive composition obtained by mixing the first component and the second component when used.
[0279] In the two-component thermally conductive composition, the mass ratio of the first component to the second component (second component / first component) is preferably 1 or a value close to 1, preferably 0.8 to 1.2, more preferably 0.9 to 1.1, and more preferably 0.95 to 1.05. Thus, by making the mass ratio of the first component to the second component 1 or a value close to 1, the preparation of the thermally conductive composition becomes easy.
[0280] In the two-component thermally conductive composition, the method for obtaining the thermally conductive composition by mixing the first component and the second component is not limited, and for example, a static mixer, a mixer having a stirring blade, a vibration stirrer, or a rotation and revolution mixer can be used.
[0281] In the two-component thermally conductive composition, the first component contains an organopolysiloxane having an alkenyl group or a methacryloyl group (alkenyl-containing organopolysiloxane) and (E) a hydrosilylation catalyst, but does not contain an organohydrogenpolysiloxane. In addition, the second component contains an organohydrogenpolysiloxane, but does not contain the (E) hydrosilylation catalyst. In addition, at least one of the first component and the second component contains (C) a thermally conductive filler. In addition, it is preferred that both the first component and the second component contain (C) a thermally conductive filler.
[0282] More specifically, the first dose contains at least one of the components (A) and (D) and the component (E), but does not contain the component (B). On the other hand, the second dose contains the component (B), but does not contain the component (E). In addition, at least one of the first dose and the second dose contains the component (C).
[0283] It is more preferred that the first agent contains at least one of the components (A) and (D), and the components (C) and (E), but does not contain the component (B). On the other hand, the second agent contains the components (B) and (C), but does not contain the component (E).
[0284] The first agent having the above structure contains the (E) hydrosilylation catalyst that promotes the addition reaction, but does not contain the organohydrogenpolysiloxane, and thus can prevent the addition reaction from proceeding before mixing with the second agent. The second agent contains the organohydrogenpolysiloxane, but does not contain the (E) hydrosilylation catalyst that promotes the addition reaction, and thus can prevent the addition reaction from proceeding before mixing with the first agent.
[0285] The organopolysiloxane containing either an alkenyl group or a methacryloyl group constituting the thermally conductive composition may be entirely contained in the first agent, but preferably a portion thereof is contained in the first agent, and the remainder thereof is contained in the second agent. More specifically, the components (A) and (D) in the thermally conductive composition may be entirely contained in the first agent, but preferably a portion of the components (A) and (D) are contained in the first agent, and the remainder of the components (A) and (D) are contained in the second agent.
[0286] In this way, by dividing the organopolysiloxane containing either an alkenyl group or a methacryloyl group into the first part and the second part, the viscosity of the first part and the second part can be easily adjusted to a desired range, and the mass ratio of the first part and the second part can be easily adjusted to 1 or a value close to 1. In addition, although the second part also contains an organohydrogenpolysiloxane, since it does not contain (E) a platinum-based curing catalyst, even if it contains an organopolysiloxane containing either an alkenyl group or a methacryloyl group, the addition reaction can be substantially prevented from proceeding during storage, etc. In addition, the second part can also contain a reaction control agent to prevent the reaction in the second part from proceeding.
[0287] When the organopolysiloxane containing either an alkenyl group or a methacryloyl group is contained in the second agent, it may be blended in the second agent as a mixture with the organohydrogenpolysiloxane. For example, the component (A) may be blended in the second agent as a mixture with the component (B).
[0288] The organohydrogenpolysiloxane constituting the thermally conductive composition is entirely contained in the second agent and is not contained in the first agent.
[0289] The (C) thermally conductive filler may be contained in any one of the first agent and the second agent for forming the thermally conductive composition. As described above, it is preferably contained in both the first agent and the second agent, and more preferably contained approximately equally. Specifically, the ratio (mass ratio) of the content of the (E) thermally conductive filler in the second agent to the content of the (C) thermally conductive filler in the first agent is preferably 0.67 to 1.5, more preferably 0.83 to 1.2, and further preferably 0.91 to 1.1. By distributing the (C) thermally conductive filler approximately equally to the first agent and the second agent, it is easy to reduce the viscosity difference between the first agent and the second agent, and it is also easy to make the mass ratio of the first agent and the second agent close to 1.
[0290] The thermally conductive composition preferably contains component (F), and component (F) may be contained in at least one of the first agent and the second agent. Among them, component (F) is preferably contained in at least the first agent, and more preferably contained in both the first agent and the second agent. When both the first agent and the second agent contain component (F), the viscosity of the first agent and the second agent can be adjusted by component (F), and the viscosity of the first agent and the second agent can be made relatively low. In addition, when component (F) contains component (F-2), it is more effective and preferred to contain component (F-2) in both the first agent and the second agent.
[0291] <Viscosity>
[0292] The viscosity VB of the binder resin contained in the thermally conductive composition at 25°C is not particularly limited, but is preferably 50 to 800 mPa·s, more preferably 80 to 600 mPa·s, and even more preferably 100 to 400 mPa·s. The viscosity VB of the binder resin refers to the viscosity of the organopolysiloxane contained in the thermally conductive composition, and is usually (A) to (D) components, or (A) to (D) components.
[0293] The viscosity of the mixture of component (D) and component (F) is the viscosity of the mixture, but when containing an organopolysiloxane other than these, it is the viscosity of the mixture containing the organopolysiloxane. The viscosity VB1 and VB2 of the binder resin of the first and second agents described later are also the viscosities of the organopolysiloxanes contained in the first and second agents, respectively.
[0294] In the two-component thermally conductive composition, the viscosity VB1 and VB2 of the binder resin contained in each of the first and second components at 25° C. are preferably 50 to 800 mPa·s, more preferably 80 to 600 mPa·s, and even more preferably 100 to 400 mPa·s.
[0295] The viscosity VB1 and VB2 of the binder resin in each of the first and second agents can be determined by mixing the organopolysiloxanes contained in each of the first and second agents and measuring the viscosity of the mixed organopolysiloxanes. The viscosity VB of the binder resin in the thermally conductive composition can also be measured in the same manner. However, in the case of a two-component thermally conductive composition, the approximate viscosity VB can also be estimated from the viscosity VB1 and VB2 of the binder resin in each of the first and second agents.
[0296] The viscosity of each organopolysiloxane at 25° C. and the viscosities VB1 and VB2 of the binder resin contained in the first and second agents can be measured as follows.
[0297] Using a rheometer (e.g., Rheometer "MCR-302e" manufactured by Anton Paar), the temperature of the sample was adjusted to 25°C using a Peltier plate. The viscosity is measured by continuously changing the shear rate within the range of 10 to 100 (1 / sec) with a cone plate of 1°. The viscosity value is the viscosity at a shear rate of 10 (1 / s).
[0298] In the two-component thermally conductive composition, the viscosity V1 and V2 of the first component and the second component at a temperature of 25° C. and a shear rate of 3.16 (1 / s) are preferably 10 to 1000 Pa·s, more preferably 50 to 700 Pa·s, and even more preferably 200 to 450 Pa·s. When the first component and the second component have such viscosities, workability can be easily improved.
[0299] The viscosity V of the thermally conductive composition of the present invention at a temperature of 25° C. and a shear rate of 3.16 (1 / s) is preferably 10 to 1000 Pa·s, more preferably 50 to 700 Pa·s, and even more preferably 200 to 450 Pa·s. Since the thermally conductive composition has such a viscosity, it has a predetermined fluidity before curing, and can be applied to narrow gaps and complex shapes.
[0300] When the thermally conductive composition is of a two-component type, the viscosity V can be determined by measuring immediately after mixing the first component and the second component, but a rough viscosity value can also be estimated from the viscosities V1 and V2 of the first component and the second component.
[0301] The difference (|V1-V2|) between the viscosity V1 of the first agent and the viscosity V2 of the second agent is preferably small from the viewpoint of easy uniform mixing of the thermally conductive composition. Specifically, the viscosity difference (|V1-V2|) between the first agent and the second agent may be, for example, 130 Pa·s or less, preferably 100 Pa·s or less, and more preferably 30 Pa·s or less. In addition, the viscosity difference (|V1-V2|) between the first agent and the second agent may be 0 Pa·s or more.
[0302] The viscosities V1 and V2 of the first and second agents can be measured by the following method.
[0303] Using a rheometer (e.g., Rheometer "MCR-302e" manufactured by Anton Paar), the temperature of the sample was adjusted to 25°C using a Peltier plate. The viscosity is measured while the shear rate is continuously changed within the range of 0.0001 to 100 (1 / s) by using parallel plates. Then, the viscosity at the above shear rate can be read.
[0304] [Thermal conductive parts]
[0305] The thermally conductive composition of the present invention is preferably used as a thermally conductive component such as a heat dissipation gap filler. The thermally conductive component is a cured product obtained by curing the thermally conductive composition.
[0306] Thermally conductive components are used inside electronic devices, etc. Specifically, the thermally conductive component is interposed between a heating element and a heat sink, and conducts the heat generated by the heating element to the heat sink, moves the heat to the heat sink, and dissipates the heat from the heat sink. Here, various electronic components such as CPUs, power amplifiers, power supplies, and semiconductor elements used inside electronic devices can be listed as heating elements. In addition, heat sinks can be listed as heat sinks, heat pumps, and metal frames of electronic devices.
[0307] In addition, the thermally conductive component can be used for electrical components, in which the heating element can be arranged in at least one of the engine room and the motor vicinity, and the present invention is particularly suitable for use in electrical components exposed to a high temperature environment of 150°C or above. In addition, it is also suitable for heat dissipation of a heating element that generates heat at 150°C or above.
[0308] The thermally conductive component can be formed by, for example, filling a thermally conductive composition in the gap between a heating element and a heat sink and curing it. Curing can be performed by heating, but is preferably performed near room temperature (for example, about 0 to 40°C, preferably about 15 to 35°C). By curing near room temperature, the thermally conductive component can be arranged inside an electronic device without applying a thermal history to the electronic components. In the case where the thermally conductive composition is a two-liquid type, it can be cured by filling the gap between the heating element and the heat sink after mixing the first agent and the second agent.
[0309] The shape of the thermally conductive component is not particularly limited, and it can be a sheet or other shapes. The thickness of the thermally conductive component is not particularly limited, and it can be used, for example, 0.3 to 5 mm, preferably 0.5 to 4 mm. In the present invention, since the thermally conductive component is flexible, if its thickness is increased (for example, more than 0.5 mm), it can exert a cushioning effect and can be used well in an environment where vibration occurs.
[0310] Example
[0311] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples at all.
[0312] <Hardness of Cured Material of Thermally Conductive Composition>
[0313] The first agent and the second agent were filled into a 50cc two-liquid parallel box (a 1:1 mixing box "CDA050-01-PP" manufactured by MIXPAC), mixed using a static mixer (static mixer for two-liquid mixing "MA6.3-12S", number of elements 6.3mm×12, inner diameter of the ejection port 1.5mm), and the obtained thermal conductive composition (volume ratio 1:1, mass ratio 1:1) was applied to the demolding surface of a demolded PET film ("SG2" manufactured by Panac) in a manner that the sample thickness was 2mm, and then another PET film ("SG2" manufactured by Panac) was pressed and fixed on the sample in a manner that the demolding surface was in contact with the sample. The sample was placed at a temperature of 25°C and a humidity of 50% RH for 24 hours to obtain a sample 1A. Using a sample obtained by punching out 5 30mm square sheets from the obtained sample 1A and overlapping them, the E-type hardness was measured as the hardness E1.
[0314] The sample 2A obtained by the same method as above was placed in a thermostatic bath set at 150°C and left in the thermostatic bath for 250 hours. After being left for 250 hours, the sample 2A was taken out of the thermostatic bath and cooled to 25°C, and the E-type hardness of the sample 2A was measured as hardness E2. E2 / E1 was calculated from the obtained hardnesses E1 and E2.
[0315] <Weight Average Molecular Weight of Component (A) and Component (D)>
[0316] The weight average molecular weight of each component was measured for the first agent and the second agent containing component (A) and component (D) (hereinafter also referred to as "sample") using a high performance liquid chromatography (HPLC)-Raman microscope composite device (LC-Raman system: manufactured by Shimadzu Corporation, chromatographic column: Shodex HK-404L (150 mm×4.6 mm I.D., 3.5 μm). Specifically, each sample was dissolved in tetrahydrofuran to prepare a 0.2 wt% solution, which was filtered through a 0.2 μm filter and used for measurement. The GPC measurement was carried out at a column temperature of 40°C, tetrahydrofuran was used as the eluent, and the flow rate of the mobile phase of the column was 0.2 mL / min. The injection volume was 10 μL, and the split ratio was 9:1. The spotting time was 20 seconds, and the spotting plate was a Hudson PL-PC-000040-P. By performing Raman measurement on different elution positions on the chromatogram that elutes in order of molecular weight, i.e. dropping elutions of different molecular weights on the spot plate and confirming the obtained Raman spectrum, it is possible to identify whether it is component (A) or component (D) and estimate the weight average molecular weight of each component. In addition, in the Raman spectrum, vinyl is identified as 1600cm -1 The peak of methacryloyl group is identified as 1640 cm -1 Next, based on the mixing ratio of the first agent and the second agent, the weight average molecular weights of the components (A) and (D) contained in the thermally conductive composition were estimated.
[0317] In addition, although the first agent and the second agent are analyzed separately, even a mixture can be analyzed in the same manner. In addition, when each raw material can be separated, the weight average molecular weight of each component can also be measured.
[0318] The raw materials used in Examples and Comparative Examples are as follows.
[0319] <Organopolysiloxane>
[0320] Organopolysiloxane 1 (component (A)): an organopolysiloxane having vinyl groups at both ends of the molecular chain (vinyl content: 0.17 mmol / g, viscosity: 410 mPa·s, weight average molecular weight: 25400)
[0321] Organopolysiloxane 2 (component (A) and component (B)): a mixture of an organopolysiloxane having vinyl groups at both ends of the molecular chain (component (A)) and an organopolysiloxane having three or more hydrosilyl groups (component (B)) (vinyl content 0.15 mmol / g, hydrosilyl content 0.19 mmol / g, viscosity 336 mPa·s, weight average molecular weight 25000, mass ratio (A) component: (B) component = 90:10)
[0322] Organopolysiloxane 3 (component (A)): an organopolysiloxane having vinyl groups at both ends of the molecular chain (vinyl content: 0.314 mmol / g, viscosity: 100 mPa·s, weight average molecular weight: 11300)
[0323] (In the organopolysiloxane 2, the component (A) does not have a hydrosilyl group, and the component (B) does not have a vinyl (alkenyl) group.)
[0324] Organopolysiloxane 4 (component (B)): an organopolysiloxane having hydrosilyl groups at both ends of the molecular chain (hydrosilyl group content: 0.329 mmol / g, viscosity: 128 mPa·s, weight average molecular weight: 6000)
[0325] Organopolysiloxane 5 (component (D)): an organopolysiloxane having a methacryloyl group at one end of the molecular chain (methacryloyl content: 0.20 mmol / g, viscosity: 65 mPa·s, weight average molecular weight: 5000)
[0326] Organopolysiloxane 6 (component (D)): an organopolysiloxane having a methacryloyl group at one end of the molecular chain (methacryloyl content: 0.10 mmol / g, viscosity: 177 mPa·s, weight average molecular weight: 10,000)
[0327] Organopolysiloxane 7: a mixture of an organopolysiloxane having a vinyl group at one end of the molecular chain (component (A), 50% by mass), an organopolysiloxane having vinyl groups at both ends of the molecular chain (component (A), 25% by mass), and an organopolysiloxane having no vinyl group (component (F), 25% by mass) (vinyl content 0.22 mmol / g, viscosity 110 mPa·s, weight average molecular weight 5000)
[0328] Organopolysiloxane 8 (component (F-1)): dimethyl silicone oil having no hydrosilylation reaction group (viscosity 101 mPa·s)
[0329] Organopolysiloxane 9 (((F-2) component): an organopolysiloxane having no hydrosilylation reaction group and having a trialkoxysilyl group at the terminal (viscosity 26 mPa·s)
[0330] Organopolysiloxane 10 (component (A)): an organopolysiloxane having vinyl groups at both ends of the molecular chain (vinyl content: 0.34 mmol / g, viscosity: 110 mPa·s, weight average molecular weight: 9200)
[0331] Organopolysiloxane 11 (component (A) and component (B)): a mixture of an organopolysiloxane having vinyl groups at both ends of the molecular chain (component (A)) and an organopolysiloxane having three or more hydrosilyl groups (component (B)) (vinyl content 0.30 mmol / g, hydrosilyl content 0.19 mmol / g, viscosity 90 mPa·s, weight average molecular weight 9200, mass ratio (A) component: (B) component = 90:10)
[0332] <Thermal conductive filler>
[0333] Alumina 1 ((C) component): spherical alumina (D50: 0.5 μm)
[0334] Alumina 2 ((C) component): spherical alumina (D50: 3 μm)
[0335] Alumina 3 ((C) component): spherical alumina (D50: 18 μm)
[0336] Alumina 4 ((C) component: spherical alumina (D50: 45) μm)
[0337] Alumina 5 (((C) component): spherical alumina (D50: 70 μm)
[0338] <Hydrosilation Catalyst>
[0339] Platinum catalyst (((E) component)
[0340] [Examples 1 to 9, Comparative Examples 1 to 4]
[0341] The first agent and the second agent were prepared according to the compounding compositions shown in the following Tables 1 to 3. Using the thermally conductive composition obtained by mixing the first agent and the second agent, various physical properties were measured and various evaluations were performed.
[0342] Table 1
[0343]
[0344] Table 2
[0345]
[0346] Table 3
[0347]
[0348] ※Total Vi+Me content 1 is the total content of alkenyl groups and methacryloyl groups relative to the total amount of organopolysiloxanes 1 to 9 in the first agent and the second agent.
[0349] ※Total Vi+Me content 2 is the total content of alkenyl groups and methacryloyl groups relative to the total amount of the thermally conductive composition (first agent and second agent).
[0350] *Total Me content 1 is the total content of methacryloyl groups relative to the total amount of organopolysiloxanes 1 to 9 in each of the first agent and the second agent.
[0351] ※Total Me content 2 is the total content of methacryloyl groups relative to the total amount of the thermally conductive composition (first agent and second agent).
[0352] ※The hydrosilyl group amount 1 is the total content of the hydrosilyl groups relative to the total amount of the organopolysiloxanes 1 to 9 in each of the first agent and the second agent.
[0353] ※The hydrosilyl group amount 2 is the total content of the hydrosilyl groups relative to the total amount of the thermally conductive composition (the first agent and the second agent).
[0354] As is apparent from the above examples, a thermally conductive member formed from a thermally conductive composition satisfying the requirements of the present invention can suppress an increase in hardness even when placed in a high-temperature environment.
[0355] In contrast, the thermally conductive components formed from the thermally conductive compositions of Comparative Examples 2 and 3 did not contain the component (D), and the hardness increase could not be suppressed under high temperature conditions. In addition, the thermally conductive composition of Comparative Example 1 could not be cured, so a thermally conductive component could not be formed, and whether the hardness increase was suppressed could not be evaluated. In addition, the weight average molecular weight M of the component (D) was wd Greater than the weight average molecular weight M of component (A) wa Comparative Example 4 cannot suppress the increase in hardness even in a high temperature environment.
Claims
1. A thermally conductive composition comprising the following ingredients: (A) an organopolysiloxane having an alkenyl group, (B) an organohydrogenpolysiloxane having a hydrosilyl group, (C) Thermally conductive filling materials, (D) a polysiloxane compound having a methacryloyl group, and (E) a hydrosilylation catalyst, The weight average molecular weight M of the component (D) wd Less than the weight average molecular weight M of the component (A) wa .
2. A thermally conductive composition comprising the following ingredients: (A) an organopolysiloxane having an alkenyl group, (B) an organohydrogenpolysiloxane having a hydrosilyl group, (C) Thermally conductive filling materials, (D) a polysiloxane compound having a methacryloyl group, and (E) a hydrosilylation catalyst, The composition is composed of a combination of a first agent and a second agent, The first agent contains at least one of the components (A) and (D) and the component (E), but does not contain the component (B). The second agent contains the component (B) but does not contain the component (E), The component (C) is contained in at least one of the first agent and the second agent, The weight average molecular weight M of the component (D) wd Less than the weight average molecular weight M of the component (A) wa .
3. The thermally conductive composition according to claim 1 or 2, wherein the weight average molecular weight M of the component (D) is wd and the weight average molecular weight M of the component (A) wa Satisfies the following formula (1): M wd ×2.3≤M wa (1)。 4. The thermally conductive composition according to claim 1 or 2, wherein the Me content and the Vi content satisfy the following formula (2) and formula (3) on a molar basis, wherein: Me content indicates the content of methacryloyl groups, Vi content indicates the content of alkenyl groups, 0.10≤α≤0.60 (2) α=Me content / (Me content+Vi content) (3).
5. The thermally conductive composition according to claim 1 or 2, wherein the content H of the hydrosilyl groups and the content Vi of the alkenyl groups satisfy the following formula (4) on a molar basis: 0.8≤H / Vi≤1.5 (4).
6. The thermally conductive composition according to claim 1 or 2, wherein the content H of the hydrosilyl groups, the content Vi of the alkenyl groups and the content Me of the methacryloyl groups satisfy the following formula (5) on a molar basis: 0.4≤H / (Vi+Me)≤1.2 (5).
7. The thermally conductive composition according to claim 1 or 2, wherein the relationship between the E-type hardness E1 after the thermally conductive composition is left at 25° C. for 24 hours and the E-type hardness E2 after the thermally conductive composition is left at 25° C. for 24 hours and further left at 150° C. for 250 hours satisfies the following formula (6): E2 / E1≤1.5 (6). 8 . The thermally conductive composition according to claim 1 , further comprising (F) an organopolysiloxane having no addition reactive group.
9. The thermally conductive composition according to claim 1 or 2, wherein the viscosity of the composition at a temperature of 25°C and a shear rate of 3.16 is 10 to 1000 Pa·s, wherein the unit of the shear rate is 1 / s. 10 . The thermally conductive composition according to claim 1 , wherein the component (C) contains aluminum oxide.
11. First dose, The thermally conductive composition is used as a thermally conductive composition containing the following components by mixing with the second component: (A) an organopolysiloxane having an alkenyl group, (B) an organohydrogenpolysiloxane having a hydrosilyl group, (C) Thermally conductive filling materials, (D) a polysiloxane compound having a methacryloyl group, and (E) a hydrosilylation catalyst, The first agent contains at least one of the components (A) and (D) and the component (E), but does not contain the component (B). By combining with the second agent, the weight average molecular weight M of the component (D) is wd Less than the weight average molecular weight M of the component (A) wa .
12. Second dose, The thermally conductive composition is used as a thermally conductive composition containing the following ingredients by mixing with the first agent: (A) an organopolysiloxane having an alkenyl group, (B) an organohydrogenpolysiloxane having a hydrosilyl group, (C) Thermally conductive filling materials, (D) a polysiloxane compound having a methacryloyl group, and (E) a hydrosilylation catalyst, The second agent contains the component (B) but does not contain the component (E), By combining with the first agent, the weight average molecular weight M of the component (D) is wd Less than the weight average molecular weight M of the component (A) wa .
13. A thermally conductive component obtained by curing the thermally conductive composition according to claim 1 or 2.
14. An electrical component, wherein the thermally conductive component obtained by curing the thermally conductive composition according to claim 1 or 2 is interposed between a heating element and a heat dissipating element. 15 . The electric component according to claim 14 , wherein the heat generating element is disposed at least one of in an engine room and near a motor.
16. The electric component according to claim 14 or 15, which is exposed to an environment of 150°C or higher.
Citation Information
Patent Citations
Thermally conductive silicone gel composition
WO2021140694A1